Development of cognitive-creative competence in students of general secondary education - Z.U.Хоjiyeva; Yulduzxon G‘аfurjanovna Mamadaliyeva (Zien Journals, 2022)
The article focuses on the pedagogical basis for the development of cognitive and creative competence in students.
Keywords: intellectual; intellectual abilities; creative; cognitive-creative; interactive game